Tissue-attached silk micro-nanofiber microporous vapor-permeable composite membrane and preparation method thereof

The use of chemical crosslinters and hyaluronic acid -in -pores in the medium -mediated calcium ions improved the wet water -resistant and transparentness of silk micr -nano fiber composite membrane, solving the performance of silk micr -nano fiber membrane in wet mechanical performance The problem of poor difference and vaporism realizes the improvement of biological applications and the biodegradability of materials.

CN119326936AActive Publication Date: 2025-01-21WUHAN TEXTILE UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411322173.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-21
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The natural silk micro-nanofiber membrane has extremely poor mechanical properties in wet state, and due to the high surface energy, the micro-nanofibers gather together during the film formation process and have poor vapor permeability, which limits its biological application.

Method used

By using calcium ions as the cross-linking medium between silk micro-nanofibers and alginate, chemical cross-linking between sodium alginate-alginate, alginate-silk micro-nanofibers, and silk micro-nanofibers-silk micro-nanofibers is formed. connection to improve the water resistance of the composite membrane. At the same time, hyaluronic acid or its salt is used as a pore-forming agent to form a nano-level porous structure and improve steam permeability.

Benefits of technology

The silk micro-nano fiber composite membrane has achieved water resistance and high vapor permeability in the wet state, improving its potential for biological applications. The material has good biocompatibility, biodegradability, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119326936A_ABST
    Figure CN119326936A_ABST
Patent Text Reader

Abstract

The invention provides a tissue-attached silk micro-nanofiber microporous vapor-permeable composite membrane and a preparation method thereof. The preparation process comprises the following steps: sequentially adding alginate, hyaluronic acid or a salt thereof and glycerol into a silk micro-nanofiber suspension to prepare a composite slurry, and then preparing the composite slurry into a silk micro-nanofiber composite prefabricated film; and finally, soaking the silk micro-nano fiber composite prefabricated membrane in a calcium ion solution for crosslinking, and soaking in deionized water for cleaning. Calcium ions are used as a cross-linking medium of the silk micro-nanofibers and the alginate, so that chemical cross-linking is generated among sodium alginate-alginate, alginate-silk micro-nanofibers and silk micro-nanofibers-silk micro-nanofibers, and the composite membrane obtains water resistance. Hyaluronic acid or a salt thereof is used as a pore-forming agent, and nano-scale micropores are formed through partial dissolution of the pore-forming agent in water, so that the vapor permeability of the composite membrane is improved. The composite membrane can be used in the fields of medical materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanofiber membrane preparation, and in particular to a tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane and a preparation method thereof. Background Art

[0002] Silk is a natural protein fiber with silk fibrils ranging from tens of nanometers to several microns. Natural silk micro-nanofibers retain the good rigidity, biocompatibility and degradability of silk, and have been studied to form films, aerogels and various composite materials for biomedical materials. However, although natural silk micro-nanofiber membranes have certain mechanical properties in a dry state, their mechanical properties in a wet state are extremely poor, which limits their application. Therefore, it is very important to cross-link silk micro-nanofibers to improve their mechanical properties in a wet state. In addition, due to their high surface energy, silk micro-nanofibers are prone to micro-nanofiber aggregation during the film-forming process, which will result in a dense surface of the membrane and poor air permeability, limiting its biological application.

[0003] In order to solve the above problems, the patent with the announcement number CN118257137A discloses a preparation method and application of a silk micro-nano fiber / non-woven fabric composite. The patent configures silk nanofibers and polysaccharide polymers into a composite slurry, and then uses the coating process to apply the composite slurry on a non-woven fabric to obtain a silk micro-nano fiber / non-woven fabric composite, which is applied to the fields of filter materials and medical dressings. However, this silk micro-nano fiber / non-woven fabric composite is not an independent silk micro-nano fiber membrane, and the addition of non-woven fabric will reduce the tissue adhesion of the silk micro-nano fiber composite membrane. At the same time, the micro-nano fiber layer of this silk micro-nano fiber / non-woven fabric composite has poor air permeability.

[0004] In the prior art, a method for preparing a composite water-resistant scaffold of silk fibroin, hyaluronic acid and sodium alginate is disclosed, specifically, silk fibroin solution, hyaluronic acid and sodium alginate are mixed into a solution, and then EDC / NHS is added to perform a cross-linking reaction to obtain a gel, and then the mixed gel is freeze-dried to obtain a composite scaffold. However, the cross-linking reagent cost of this cross-linking reaction method is high, the cross-linking rate is slow, and the freeze-drying process used at the same time is difficult to mass produce. In addition, there is a related document reporting a method for preparing a porous sodium alginate / cellulose nanofiber composite hydrogel microsphere and using it in sewage purification, specifically, cellulose nanofibers, sodium alginate and pore-forming agent polyethylene glycol are configured into a composite suspension, and then added dropwise to a calcium ion solution to cross-link into a hydrogel microsphere, and finally prepared into a porous hydrogel microsphere by washing. However, since the sodium alginate / cellulose nanofiber composite hydrogel microsphere is used for water purification, it can be seen that the pore-forming agent polyethylene glycol has been substantially completely dissolved, and will not give the hydrogel microsphere further functions.

[0005] In view of this, it is necessary to design an improved silk micro-nano fiber composite membrane, in particular, to design a tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane. Summary of the invention

[0006] The present invention provides a tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane and a preparation method thereof. The present invention uses calcium ions as a medium for cross-linking silk micro-nano fibers and alginate, so that chemical cross-linking occurs between sodium alginate-alginate, alginate-silk micro-nano fibers, and silk micro-nano fibers-silk micro-nano fibers, so that the composite membrane obtains water resistance. The raw materials used in the present invention have good biocompatibility and are biodegradable, and can be used in the fields of medical materials.

[0007] To achieve the above-mentioned purpose of the invention, the present invention provides a method for preparing a tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane, comprising the following steps:

[0008] S1, sequentially adding alginate, hyaluronic acid or its salt, and glycerol to the silk micro-nanofiber suspension, and mixing them evenly to obtain a composite slurry;

[0009] S2, preparing the composite slurry obtained in step S1 into a silk micro-nano fiber composite prefabricated membrane;

[0010] S3, soaking the silk micro-nano fiber composite prefabricated membrane obtained in step S2 in a calcium salt solution with a mass fraction concentration of 0.5%wt-1.5%wt for 5-30 minutes to carry out a cross-linking reaction, and then rinsing with deionized water and drying to obtain a tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane.

[0011] Through the cross-linking reaction, chemical cross-linking between sodium alginate and sodium alginate, sodium alginate and silk micro-nanofibers, and silk micro-nanofibers and silk micro-nanofibers is formed inside the composite film, thereby obtaining water resistance. At the same time, in this process, the sodium hyaluronate and glycerol in the composite film will be released, so that a nano-scale porous structure is formed inside, and the air permeability is improved.

[0012] As a further improvement of the present invention, in step S1, the amount of alginate is 5%-15% of the mass of the silk micro-nano fibers, the amount of hyaluronic acid or its salt is 20%-80% of the mass of the silk micro-nano fibers, and the amount of glycerol is 25%-35% of the mass of the silk micro-nano fibers. The addition of glycerol can avoid problems such as wrinkles and ruptures of the silk micro-nano fiber composite prefabricated membrane.

[0013] As a further improvement of the present invention, in step S2, the silk micro-nano fiber composite prefabricated membrane is prepared by a coating method, a casting method, etc., preferably a coating method.

[0014] As a further improvement of the present invention, in step S3, rinsing with deionized water means: soaking the calcium ion cross-linked silk micro-nano fiber composite prefabricated membrane in deionized water for 1-200 hours. This process removes the residual calcium ions and glycerol on the surface, while the residual hyaluronic acid or its salt in the silk micro-nano fiber composite membrane will continue to dissolve, which is conducive to the further formation of the porous structure.

[0015] As a further improvement of the present invention, hyaluronate refers to one or a combination of different kinds of sodium hyaluronate, potassium hyaluronate, etc.

[0016] As a further improvement of the present invention, the silk micro-nano fibers are natural silk extracts and have a diameter of 30 to 2000 nm.

[0017] The present invention also provides a tissue-adherent silk micro-nano fiber microporous vapor-permeable composite membrane, which is prepared by the preparation method described in any of the technical schemes in the aforementioned technical schemes, wherein chemical crosslinks between sodium alginate-sodium alginate, sodium alginate-silk micro-nano fiber, and silk micro-nano fiber-silk micro-nano fiber are formed inside the tissue-adherent silk micro-nano fiber microporous vapor-permeable composite membrane, and the tissue-adherent silk micro-nano fiber microporous vapor-permeable composite membrane has a nano-scale porous structure inside, and the pore size range is 1-800nm.

[0018] As a further improvement of the present invention, the tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane contains hyaluronic acid or its salt that is not completely dissolved out during the preparation process. The hyaluronic acid or its salt that is not completely dissolved out in the composite membrane is not toxic, but can improve the water absorption, water retention, biological activity and other properties of the composite membrane. The composite membrane can be tightly adhered to mammalian tissues, including skin, liver, heart, etc.

[0019] As a further improvement of the present invention, the thickness of the tissue-adherent silk micro-nano fiber microporous vapor-permeable composite membrane is 2 μm-15 μm.

[0020] As a further improvement of the present invention, the tissue-adherent silk micro-nano fiber microporous vapor-permeable composite membrane has a vapor permeability greater than 500 g / (m 2 ·24h).

[0021] The beneficial effects of the present invention are:

[0022] (1) The present invention utilizes calcium ions as a medium for cross-linking silk micro-nano fibers and alginate, so that chemical cross-linking occurs between sodium alginate-alginate, alginate-silk micro-nano fibers, and silk micro-nano fibers-silk micro-nano fibers, thereby making the silk micro-nano fiber composite membrane water-resistant.

[0023] (2) The present invention uses hyaluronic acid or its salt as a pore-forming agent, and forms nano-scale micropores through the dissolution of the pore-forming agent in water, thereby improving the vapor permeability of the composite film. At the same time, the hyaluronic acid or its salt that is not completely dissolved in the composite film is not toxic, but can improve the water absorption, water retention, biological activity and other properties of the composite film.

[0024] (3) The present invention utilizes the rigidity of silk micro-nano fibers, the roughness of the surface of the silk micro-nano fiber membrane, and the weak curling effect of the silk micro-nano fiber membrane that tends to adhere to the tissue during the drying process to prepare a polymer membrane with high tissue adhesion.

[0025] (4) The raw materials used in the present invention have good biocompatibility and are biodegradable, and the preparation method provided by the present invention is suitable for large-scale production. The tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane prepared by the present invention can be used in the field of medical materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is an underwater display of the silk micro-nano fiber composite prefabricated membrane prepared in Example 1 and the tissue-adherent silk micro-nano fiber microporous vapor-permeable composite membrane after cross-linking and immersion.

[0027] Figure 2 This is a test diagram of the water resistance of the tissue-adherent silk micro-nanofiber microporous vapor-permeable composite membrane prepared in Example 1.

[0028] Figure 3 This is a SEM image of the surface of the tissue-adherent silk micro-nano fiber microporous vapor-permeable composite membrane prepared in Example 1; wherein, the scale of Figure a is 2 μm; and Figure b is an enlarged view of Figure a, with a scale of 500 nm.

[0029] Figure 4 This is a SEM image of the cross section of the tissue-adherent silk micro-nanofiber microporous vapor-permeable composite membrane prepared in Example 1, with a scale of 5 μm.

[0030] Figure 5 This is a demonstration diagram of the tissue-adhesive silk micro-nanofiber microporous vapor-permeable composite membrane prepared in Example 1 being attached to human skin.

[0031] Figure 6 This is a SEM image of the surface of the silk micro-nano fiber composite membrane prepared in Comparative Example 1; wherein, the scale of Figure a is 2 μm; Figure b is an enlarged view of Figure a, with a scale of 500 nm.

[0032] Figure 7 This is a physical display picture of the silk micro-nano fiber composite prefabricated membrane prepared in Comparative Example 2.

[0033] Figure 8This is a skin adhesion test of the sodium alginate film prepared in Comparative Example 3.

[0034] Fig. 9 This is a water resistance test of the composite membrane prepared in Comparative Example 7. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0036] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.

[0037] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0038] As a natural polysaccharide polymer, alginate has good biocompatibility and biodegradability, and has good film-forming properties. However, during the drying process, the molecular chains of pure alginate membranes will move rapidly and entangle, and will curl in the opposite direction of the attached tissue, resulting in poor tissue adhesion. Alginate can be added to silk micro-nanofibers to prepare composite membranes, which can promote the formation and functionalization of silk micro-nanofiber membranes. However, the introduction of high molecular polymers such as alginate will block the pores between the fibers, making the silk micro-nanofiber membranes more dense, resulting in a significant decrease in air permeability.

[0039] In this regard, the present invention uses hyaluronic acid or its salt as a pore-forming agent, and forms nano-scale micropores through the dissolution of the pore-forming agent in water, thereby improving the vapor permeability of the composite film. At the same time, the hyaluronic acid or its salt that is not completely dissolved out of the composite film is not toxic but has biological activity. The present invention uses the rigidity of silk micro-nano fibers, the roughness of the surface of the silk micro-nano fiber membrane, and the weak curling effect of the silk micro-nano fiber membrane that tends to adhere to the tissue during the drying process to prepare a polymer membrane with high tissue adhesion.

[0040] The present invention provides a method for preparing a tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane, comprising the following steps:

[0041] S1. Preparation of silk micro-nano fiber composite slurry:

[0042] The degummed silk is placed in a swelling solution (a mixed solution of calcium nitrate, ethanol and water, the volume ratio of ethanol to water is 1:2-6, and the ratio of the mass of calcium nitrate to the total volume of ethanol and water is 1-10g:100mL) and placed in a 50-80°C oven for 60-80h to swell the silk to weaken the binding force between the nanofibrils in the silk. After being taken out, it is washed with deionized water for 3 times, and placed in a wall crushing machine with a bath ratio of 1g:100-200mL (i.e. 1g silk: 100-200mL water) at a rotation speed of 10000-50000r / min. It is mechanically treated for 80-100min, the silk fibers are mechanically crushed, filtered three times with a filter, and freeze-dried to obtain silk micro-nanofibers.

[0043] An appropriate amount of silk micro-nano fibers and deionized water were added into a homogenizer to prepare a nanofiber suspension with a mass fraction concentration of 1.5 wt%.

[0044] An appropriate amount of alginate and deionized water were added into a beaker and stirred evenly to prepare an alginate solution with a mass fraction concentration of 1.5 wt %.

[0045] Add appropriate amount of hyaluronic acid or its salt and deionized water into a beaker and stir evenly to prepare a hyaluronic acid or its salt solution with a mass fraction concentration of 1.5wt%. The hyaluronic acid salt is one or more combinations of sodium hyaluronate, potassium hyaluronate, etc.

[0046] Then, appropriate amounts of 1.5 wt% nanofiber suspension, 1.5 wt% alginate solution, 1.5 wt% hyaluronic acid or its salt solution, and glycerol are added into the beaker and stirred evenly to obtain a silk micro-nano fiber composite slurry.

[0047] The amount of sodium alginate is 5%-15% of the mass of the silk micro-nano fibers, the amount of sodium hyaluronate is 20%-80% of the mass of the silk micro-nano fibers, and the amount of glycerol is 25%-35% of the mass of the silk micro-nano fibers.

[0048] The silk micro-nano fiber is a natural silk extract with a diameter of 30 to 2000 nm. The silk can be domestic silk or wild silk.

[0049] S2. The composite slurry obtained in step S1 is prepared into a silk micro-nano fiber composite prefabricated membrane.

[0050] The silk micro-nano fiber composite prefabricated membrane is prepared by a coating method, a casting method, etc., preferably the coating method.

[0051] For example, the composite slurry obtained in step S1 is coated on the plate with a scraper, dried, and peeled off to obtain a silk micro-nano fiber composite prefabricated membrane.

[0052] S3. Calcium ion cross-linking and immersion:

[0053] The silk micro-nano fiber composite prefabricated membrane obtained in step S2 is immersed in a calcium salt solution with a mass fraction concentration of 0.5wt%-1.5wt% for crosslinking for 5-30 minutes. The calcium salt is a soluble calcium salt, such as calcium chloride, calcium nitrate, etc., or a combination thereof.

[0054] In this process, chemical crosslinks between sodium alginate and sodium alginate, sodium alginate and silk micro-nanofibers, and silk micro-nanofibers and silk micro-nanofibers are formed inside the silk micro-nanofiber composite membrane, making the composite membrane water-resistant. At the same time, hyaluronic acid or its salt and glycerol in the composite membrane are released, forming a nano-scale porous structure inside, thereby improving its vapor permeability.

[0055] Then, the membrane is washed with deionized water for 1-200 hours to obtain a tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane. In this process, the calcium ions and glycerol remaining on the surface of the silk micro-nano fiber composite membrane will be removed, and the sodium hyaluronate remaining inside will continue to dissolve, which is conducive to the further formation of the porous structure of the membrane.

[0056] The tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane is prepared by the above preparation method. The thickness of the composite membrane is 2 μm-15 μm. The tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane has a nano-scale porous structure inside, and the pore size ranges from 1 to 800 nm.

[0057] The tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane contains hyaluronic acid or its salt that is not completely dissolved during the preparation process. The hyaluronic acid or its salt that is not completely dissolved in the composite membrane is not toxic but has biological activity. The composite membrane can be tightly adhered to mammalian tissues, including skin, liver, heart, etc.

[0058] The tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane has a vapor permeability greater than 500 g / (m 2 ·24h).

[0059] The present invention is described in detail below with reference to specific embodiments.

[0060] Example 1

[0061] A method for preparing a tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane comprises the following steps:

[0062] S1. Preparation of silk micro-nano fiber composite slurry:

[0063] 5 g of degummed silk was placed in a swelling solution (a mixed solution of calcium nitrate, ethanol and water, with a volume ratio of ethanol to water of 1:3 and a calcium nitrate content of 5 g:100 mL) and placed in a 60°C oven for 72 h. After being taken out, it was washed three times with deionized water and placed in a wall breaking machine with a blade speed of 36,000 r / min at a bath ratio of 1 g:1200 mL. It was mechanically treated for 90 min, filtered three times with a filter, and freeze-dried to obtain silk micro-nanofibers.

[0064] Then, 1.5 g of dry silk micro-nanofibers were dissolved in 98.5 g of deionized water and mixed in a homogenizer at a speed of 800 rpm for 5 minutes to obtain a silk micro-nanofiber suspension with a mass fraction concentration of 1.5 wt%; then, 10 g of sodium alginate solution with a mass fraction concentration of 1.5 wt%, 40 g of sodium hyaluronate solution with a mass fraction concentration of 1.5 wt%, and 0.45 g of glycerol were added to the silk micro-nanofiber suspension in sequence, and the mixture was slowly stirred at a speed of 200 rpm for 24 hours to obtain a silk micro-nanofiber composite slurry.

[0065] At this time, in the silk micro-nano fiber composite slurry, the content of sodium alginate is 10% of the mass of the silk micro-nano fibers, the content of sodium hyaluronate is 40% of the mass of the silk micro-nano fibers, and the content of glycerol is 30% of the mass of the silk micro-nano fibers.

[0066] The diameter of silk micro-nanofibers is mainly 500nm.

[0067] S2. Coating:

[0068] The film was coated on an aluminum plate with a coating thickness of 1000 μm at a coating speed of 0.02 m / s, and then dried and peeled off in an oven at 60° C. to obtain a silk micro-nano fiber composite prefabricated membrane.

[0069] S3. Calcium ion cross-linking and immersion:

[0070] The silk micro-nano fiber composite prefabricated membrane obtained in step S2 is soaked in a calcium chloride solution with a mass fraction concentration of 1wt% for crosslinking for 15min. Then the silk micro-nano fiber composite membrane is taken out and soaked in deionized water for 72h. In this process, the water is changed every 8h, thereby obtaining a tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane, such as Figure 1 shown.

[0071] Figure 2 The water resistance test results of the tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane prepared in Example 1. It can be seen that the composite membrane is still stable in water after being immersed for 24 hours, indicating that it has a certain degree of water resistance.

[0072] Figure 3This is a SEM image of the surface of the tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane prepared in Example 1. It can be seen that the surface of the tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane has a large number of nano-scale micropores with a pore size range of 1-600nm, and the surface is relatively rough.

[0073] Figure 4 This is a SEM image of the cross section of the tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane prepared in Example 1. It can be seen that the thickness of the tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane is about 7 μm.

[0074] Figure 5 This is a diagram showing that the composite film prepared in Example 1 can be attached to human skin.

[0075] The demonstration process is: the wet composite film prepared in Example 1 is attached to the skin of a human arm for 30 minutes, and then the composite film is peeled off.

[0076] It can be seen that the tissue-adhesive silk micro-nanofiber microporous vapor-permeable composite membrane can be laid flat on the human skin under humid conditions. After drying, it will stick tightly to the human skin and will not fall off easily. It can be removed after 30 minutes of sticking and will not cause allergies to the human skin.

[0077] The air permeability test of the tissue-adherent silk micro-nano fiber microporous vapor-permeable composite membrane prepared in Example 1 was performed:

[0078] S1. Take out a test tube with a diameter of 1 cm, and then add deionized water to a distance of 3 cm from the mouth of the test tube.

[0079] S2. Then, the tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane is covered on the surface of the test tube mouth, sealed with a sealing tape, and then weighed.

[0080] S3. Place the test tube of S2 in an environment of 37°C and 50%±10% relative humidity for 24 hours, then take it out and weigh it.

[0081] The calculation shows that its vapor permeability is about 650g / (m 2 ·24h).

[0082] Comparative Example 1

[0083] The main difference between Comparative Example 1 and Example 1 is that the pore-forming agent sodium hyaluronate is not used in step S1, and the other parts are substantially the same as Example 1 and will not be described again.

[0084] Figure 6This is a SEM image of the surface of the silk micro-nano fiber composite membrane prepared in Comparative Example 1. It can be seen that the surface of the silk micro-nano fiber composite membrane prepared without adding sodium hyaluronate is relatively dense, and at the same time, there are fewer nanopores and smaller pore sizes.

[0085] The air permeability of the silk micro-nano fiber composite membrane prepared in Comparative Example 1 was tested, and the calculation showed that its air permeability was about 410 g / (m 2 ·24h), which is much lower than the vapor permeability of Example 1.

[0086] It can be seen that the vapor permeability of the composite film can be improved by adding sodium hyaluronate as a pore-forming agent.

[0087] In addition, the water absorption rate of Example 1 and Comparative Example 1 was tested, and the results were as follows:

[0088]

[0089] It can be seen from the experimental results that, in addition to being used as a pore-forming agent, some of the residual sodium hyaluronate can also improve the additional functions of the composite film, such as improving the water absorption performance of the composite film.

[0090] Comparative Example 2

[0091] The main difference between Comparative Example 2 and Example 1 is that glycerol is not added in step S1, and the other steps are substantially the same as those in Example 1, which will not be described in detail here.

[0092] Figure 7 This is a physical display picture of the silk micro-nano fiber composite prefabricated membrane prepared in Comparative Example 2.

[0093] It can be seen that the silk micro-nano fiber composite prefabricated membrane prepared without adding plasticizer glycerol has wrinkles and cracks, which is not conducive to practical application.

[0094] Comparative Example 3

[0095] Compared with Example 1, Comparative Example 3 is mainly different in that no silk micro-nano fibers are added.

[0096] Specifically, 1.5 g of sodium alginate was dissolved in 98.5 g of deionized water and stirred evenly to obtain a sodium alginate solution with a mass fraction concentration of 1.5 wt%; then, 40 g of a sodium hyaluronate solution with a mass fraction concentration of 1.5 wt% and 0.45 g of glycerol were added to the sodium alginate solution, and the mixture was slowly stirred at a speed of 200 rpm for 24 hours to obtain a sodium alginate composite slurry.

[0097] At this time, in the sodium alginate composite slurry, the content of sodium hyaluronate accounts for 40% of the mass of sodium alginate, and the content of glycerol accounts for 30% of the mass of sodium alginate.

[0098] S2. Casting:

[0099] 7.5 g of sodium alginate composite slurry was weighed and poured into a culture dish with a diameter of 10 cm, and then dried and peeled off to obtain a sodium alginate composite prefabricated membrane.

[0100] S3. Calcium ion cross-linking and immersion:

[0101] The sodium alginate composite prefabricated membrane obtained in step S2 is soaked in a calcium chloride solution with a mass fraction concentration of 1wt% for crosslinking for 15min. Then the silk micro-nano fiber composite membrane is taken out and soaked in deionized water for 72h, wherein the water is changed every 8h during the process, thereby obtaining a sodium alginate membrane.

[0102] Figure 8 This is a skin adhesion test of the sodium alginate film prepared in Comparative Example 3.

[0103] The demonstration process is: the sodium alginate film prepared in Comparative Example 3 in a wet state is attached to the skin of a human arm for 30 minutes, and then the sodium alginate film is peeled off.

[0104] Depend on Figure 8 It can be seen that although the sodium alginate film can be laid flat on the human skin under wet conditions, it will show serious wrinkling of the reverse attached tissue after drying, and may even cause small red spots on the human skin.

[0105] Examples 2-3 and Comparative Examples 4-7

[0106] The difference between Examples 2-3 and Comparative Examples 4-7 and Example 1 is that the amounts of alginate, sodium hyaluronate and glycerol in step S1 are changed, as shown in the following table. The rest are substantially the same as Example 1 and will not be described again.

[0107] The mass fractions of the silk fibroin solutions in Examples 5-7 are shown in the following table.

[0108]

[0109]

[0110] The tissue-adherent silk micro-nano fiber microporous vapor-permeable composite membranes prepared in Examples 1-3 and Comparative Examples 1 and 4-6 were subjected to air permeability tests and wet mechanical property tests, and the results are shown in the following table.

[0111]

[0112] Fig. 9The water resistance test result of the composite membrane prepared in Comparative Example 7. As can be seen from the figure, too low a dosage of sodium alginate will lead to decreased water resistance of the silk micro-nano fiber composite membrane, and the wet mechanical strength of the membrane is extremely poor, and mechanical property tests and air permeability tests cannot be performed.

[0113] It should be noted that some comparative examples have characterized or demonstrated obvious shortcomings, so comprehensive testing is not performed.

[0114] Experiments show that within a certain range, as the amount of hyaluronic acid or its salt increases, the vapor permeability of the composite membrane increases. This is mainly because the dissolution of transparent hyaluronic acid or its salt creates more and larger micropores for the silk micro-nano fiber composite membrane, which is conducive to the permeation of water vapor. However, the increase in the amount of hyaluronic acid or its salt will cause the mechanical properties of the composite membrane to decrease. In particular, when the amount of hyaluronic acid or its salt accounts for more than 80% of the mass ratio of silk micro-nano fibers, the mechanical properties of the composite membrane will seriously decrease, which is not conducive to practical application. This is because excessive hyaluronic acid or its salt will seriously damage the structure of the silk micro-nano fiber composite membrane.

[0115] In addition, the experimental results show that as the amount of alginate decreases, the air permeability of the composite membrane will also increase, because the reduced use of alginate can make the silk micro-nano fiber membrane produce more nanopores. However, as the amount of alginate further decreases, the mechanical properties of the composite membrane will also decrease, because the reduced use of alginate will reduce the bonding effect inside the composite membrane. In particular, when the amount of alginate is less than 5% of the mass of the silk micro-nano fiber, the composite membrane may lose its water resistance.

[0116] In summary, the present invention utilizes calcium ions as a medium for cross-linking silk micro-nano fibers and alginate, so that chemical cross-linking occurs between sodium alginate-alginate, alginate-silk micro-nano fibers, and silk micro-nano fibers-silk micro-nano fibers, so that the composite film obtains water resistance. The present invention utilizes hyaluronic acid or its salt as a pore-forming agent, and forms nano-scale micropores through the dissolution of the pore-forming agent in water, thereby improving the vapor permeability of the composite film. At the same time, the hyaluronic acid or its salt that is not completely dissolved out of the composite film can improve the water absorption, water retention, biological activity and other properties of the composite film. The present invention utilizes the rigidity of silk micro-nano fibers, the roughness of the surface of the silk micro-nano fiber membrane, and the weak curling effect of the silk micro-nano fiber membrane that tends to adhere to the tissue during the drying process to prepare a polymer film with high tissue adhesion. The raw materials used in the present invention have good biocompatibility and are biodegradable.

[0117] The preparation method provided by the present invention is suitable for large-scale production. The tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane prepared by the present invention can be used in the fields of medical materials and the like.

[0118] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane, characterized in that: The steps include: S1, sequentially adding alginate, hyaluronic acid or its salt, and glycerol to the silk micro-nanofiber suspension, and mixing them evenly to obtain a composite slurry; S2, preparing the composite slurry obtained in step S1 into a silk micro-nano fiber composite prefabricated membrane; S3, soaking the silk micro-nano fiber composite prefabricated membrane obtained in step S2 in a calcium salt solution with a mass fraction concentration of 0.5%wt-1.5%wt for 5-30 minutes to carry out a cross-linking reaction, and then rinsing with deionized water and drying to obtain a tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane.

2. The method for preparing the tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane according to claim 1, characterized in that: In step S1, the amount of alginate is 5%-15% of the mass of the silk micro-nano fibers, the amount of hyaluronic acid or its salt is 20%-80% of the mass of the silk micro-nano fibers, and the amount of glycerol is 25%-35% of the mass of the silk micro-nano fibers.

3. The method for preparing the tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane according to claim 1, characterized in that: In step S2, the silk micro-nano fiber composite prefabricated membrane is prepared by a coating method or a casting method.

4. The method for preparing the tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane according to claim 1, characterized in that: In step S3, rinsing with deionized water means: soaking the silk micro-nano fiber composite prefabricated membrane after calcium ion cross-linking in deionized water for 1-200 hours to remove the residual calcium ions and glycerol on the surface of the silk micro-nano fiber composite membrane. At the same time, the residual hyaluronic acid or its salt in the silk micro-nano fiber composite membrane will further dissolve, and the microporous structure of the composite membrane will be further formed.

5. The method for preparing the tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane according to claim 1, characterized in that: The hyaluronate is one or both of sodium hyaluronate and potassium hyaluronate.

6. The method for preparing the tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane according to claim 1, characterized in that: The silk micro-nano fiber is extracted from natural silk and has a diameter of 30 to 2000 nm.

7. A tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane, characterized in that: According to the preparation method according to any one of claims 1 to 6, the tissue-adherent silk micro-nano fiber microporous vapor-permeable composite membrane has chemical crosslinks between sodium alginate-sodium alginate, sodium alginate-silk micro-nano fiber, and silk micro-nano fiber-silk micro-nano fiber formed inside, and the tissue-adherent silk micro-nano fiber microporous vapor-permeable composite membrane has a nano-scale porous structure inside, and the pore size range is 1-800nm.

8. The tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane according to claim 7, characterized in that: The tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane contains hyaluronic acid or its salt which is not completely dissolved during the preparation process.

9. The tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane according to claim 7, characterized in that: The thickness of the tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane is 2 μm-15 μm.

10. The tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane according to claim 7, characterized in that: The tissue-adhesive silk micro-nano fiber microporous vapor-permeable composite membrane has a vapor permeability greater than 500 g / (m 2 ·24h).

Citation Information

Patent Citations

  • Nano-silver, chitosan and fibroin compound biological dressing and preparation method thereof

    CN105664225A

  • Fibroin-based composite hydrogel scaffold as well as preparation method and application thereof

    CN114652891A

  • Silk micro-nanofiber / non-woven fabric compound as well as preparation method and application thereof

    CN118257137A

  • Anti bacteria natural silk composite nano-fiber material and its preparation method

    CN1904159A

  • Nano copolymer fibrous membrane material capable of being biodegraded and absorbed and preparation process and use thereof

    CN1961974A